Sorghum bicolor (L.) Moench ISS 1320 - GLIS of the ITPGRFA (International Crop Research Institute for the Semi-Arid Tropics, 2022)
Plant Genetic Resource.
Taxonomy: Sorghum bicolor (L.) Moench
Common name(s): Sorghum
Conserved by: International Crops Research Institute for the Semi-Arid Tropics (ICRISAT), India
Local sample unique identifier: ISS 1320
Method of creation: Acquisition
Date: 2012-01-01
Historical: No
Biological status: Traditional cultivar/landrace
MLS status: Included
Keywords: Plant Genetic Resource for Food and Agriculture; FOS: Biological sciences; FOS: Agriculture, forestry, and fisheries